2004
DOI: 10.1007/s00420-004-0518-1
|View full text |Cite
|
Sign up to set email alerts
|

Is there an increased risk of knee osteoarthritis among farmers? A population-based case?control study

Abstract: Work in building and construction occupations, but not in farming, was associated with an increased risk of knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 23 publications
(35 reference statements)
0
59
0
2
Order By: Relevance
“…9,13,14,19,25,26,29,31,34,37,39,40,43 All three cohort studies reported significant results for men. 9,21,33 Considering the consistent results across all Fifteen studies examined the relationship between occupational physical loading tasks and knee OA in women, including two cohort studies, 9,21 nine case control studies, 13,14,25,26,29,30,32,40,44 and four cross-sectional studies. 19,39,41,42 Nine studies showed a significantly positive association between an occupational exposure and knee OA in women (OR ¼ 1.4-7.3).…”
Section: Occupational Physical Loading By Sexmentioning
confidence: 90%
See 2 more Smart Citations
“…9,13,14,19,25,26,29,31,34,37,39,40,43 All three cohort studies reported significant results for men. 9,21,33 Considering the consistent results across all Fifteen studies examined the relationship between occupational physical loading tasks and knee OA in women, including two cohort studies, 9,21 nine case control studies, 13,14,25,26,29,30,32,40,44 and four cross-sectional studies. 19,39,41,42 Nine studies showed a significantly positive association between an occupational exposure and knee OA in women (OR ¼ 1.4-7.3).…”
Section: Occupational Physical Loading By Sexmentioning
confidence: 90%
“…These include two cohort studies, 21,33 five case-control studies, 11,13,37,40,44 and five cross-sectional studies. 17,18,23,28,42 Nine studies reported a positive relationship between knee OA and occupation (OR ¼ 1.4-4.7), 11,13,17,21,23,37,40,44 but only three scored high on methodological quality. 13,37,40 Many studies in this subgroup are older and have procedural flaws, such as failing to control for relevant covariates 17,21 or low participation rates.…”
Section: Occupational Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, kneeling, heavy lifting, and workload attributed to both kneeling and heavy listing are known to increase the risk of degenerative osteoarthritis of the knee (Sandmark et al, 2000;Manninen et al, 2002;Baker et al, 2003;Rytter et al, 2009;Dahaghin et al, 2009;Klussmann et al, 2010;Lau et al, 2000;Coggen et al, 2000;Holmberg et al, 2004;Rossignol, 2004;Jensen, 2008;Amin et al, 2008;Andersen et al, 2012;Ezzat et al, 2013). In addition, Rossignol (2003) has reported that bluecollar workers have higher risk of osteoarthritis of the knee compared to white-collar workers (Rossignol, 2003).…”
Section: Effect Of Workload On Knee Osteoarthritismentioning
confidence: 99%
“…Male farm workers, forestry workers and postal workers have not demonstrated an increased risk of knee osteoarthritis [14]. Previous studies have shown a correlation between the physical demands of knee bending/squatting and the development of osteoarthritis [15].…”
Section: Introductionmentioning
confidence: 99%